Evaluation of the Strengthening of Nigeria's Justice System Integrity and Capacity Selective States : The Supreme Court of Nigeria's Analysis Principle - Ajiteru S.A.R; Sulaiman T.H; Abalaka J.N (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The technical assessment project's major goals were to gain a comprehensive understanding of the integrity and capacity status of the justice sector in Nigeria. Nigeria's existing levels of access to justice, the promptness and caliber of justice delivery, the independence and impartiality of the judiciary, corruption, and public confidence in justice sector institutions were all examined in this study. In three pilot states, respondents were given pre-formulated questions intended to elicit their perceptions and experiences related to a particular day in court. Both narrative and graphic formats are used to present the interview results. The report presents key findings relating to the target groups' perceptions and experiences regarding the delivery of justice and the integrity of the justice system, and it identifies the underlying causes of the issues by drawing on and analyzing the data, paying particular attention to the reinforcing interdependencies of the various problems. The study, which is structured around 17 major findings, provides a thorough examination of the information acquired from the interviews. Based on the main conclusions, it offers comprehensive policy recommendations for judicial reform initiatives that will improve public trust in the legal system, increase the independence, fairness, and impartiality of the judiciary, improve accessibility to the courts, improve the efficiency of justice delivery, and reduce corruption in the legal system.